Sistem Informasi Perpustakaan Sman 4 Tambun Selatan Dengan Fitur Qr-Code Berbasis Web - Maryam Hafiizhatul Kariimah; Agus Setiawan; Onki Alexander (Universitas PGRI Madiun, 2021)
The library is a source of learning that must be owned by every school and even college. Based on the results of interviews regarding the problems faced by SMAN 4 TAMBUN SELATAN, all activities carried out in the library are still using the manual system, so it takes a long time to search for data. so that the problem will have an impact on the process of making library reports that must be reported every month. To solve this problem, a change is needed from a manual system to a computerized system. The purpose of this research is to develop a web-based library management information system. Therefore for improve a service at school. This information system consists of 2 actors, namely the library admin and students. The method used to carry out this development is the waterfall method which consists of needs analysis, system design, implementation, system testing, and system maintenance. This system was developed using the PHP programming language, the database used is MySQL. The testing technique used is Black-Box Testing (Alpha) and UAT User Acceptance Testing (Beta). The results of the Black-Box Testing with 25 test scenarios can be concluded that the application has been running well with a success percentage of 100% and the results of the UAT based on the level of user acceptance of the entire system are very good, with a percentage of 92%.